Organizational mechanism of state management of social services in territorial communities - Sukhova, Ksenia; Borodin, Yevgeniy; Tarasenko, Tetiana; Komarova, Kateryna; Akimova, Lіudmyla; Akimov, Oleksandr (My University, 2022)
In a welfare state, an important role is played by the activities of municipalities in the provision of services in the field of social services. At the same time, the system of social services is partially or completely based on local structures, various models of organization of which have received practical implementation. Such models are based on various approaches determined by the features of the social support system inherent in a given country, the system of municipal government, and the territorial organization of the state. In recent years, in economically developed countries, the so-called transformational approach has been formed, which implies social work in the local community, that contributes to the empowerment of citizens with greater powers and the possibility of real influence, development and liberalization. Since this term is applied to most countries that are developing a model of the welfare state, it can be used both in theoretical developments and in the practice of social work in the community. It emphasizes the importance of democratic methods and tasks in the development of the local community, as well as the forms and methods of social work itself.
Keywords: communities; management; social services; welfare